End-stage Renal Disease and Risk of Active Tuberculosis: a Nationwide Population-Based Cohort Study - Min, Jinsoo; Kwon, Soon Kil; Jeong, Hye Won; Han, Joung-Ho; Kim, Yeonkook Joseph; Kang, Minseok; Kang, Gilwon (Journal of Korean medical science, 2018)
The converging epidemics of tuberculosis (TB) and end-stage renal disease (ESRD) have generated a significant public health burden, however, previous studies have been limited to a small number of patients. This nationwide cohort study aimed to assess the rate of developing active TB among patients receiving dialysis for ESRD. The Korean national health insurance database was used to identify patients receiving dialysis for new-onset ESRD during 2004-2013, who were propensity score matched to an equivalent number of non-dialysis subjects from the general population. The incidences of active TB in the ESRD and control cohorts were calculated for 2004-2013, and multivariable Cox proportional hazards model was used to evaluate the ESRD-related risk of active TB. During 2004-2013, 59,584 patients received dialysis for newly diagnosed ESRD. In the dialysis and control cohorts, 457 (0.8%) and 125 (0.2%) cases of active TB were detected, respectively. Patients with ESRD were associated with a significantly higher risk of active TB compared to the controls (incidence rate ratio, 4.80). The ESRD cohort had an independently elevated risk of active TB (adjusted hazard ratio, 4.39; 95% confidence interval, 3.60-5.37). We found that patients receiving dialysis for ESRD had an elevated risk of active TB. These results highlight the need for detailed and well-organised guidelines for active TB screening among patients with ESRD.